Annexin‐1 is an oncogene in glioblastoma and causes tumour immune escape through the indirect upregulation of interleukin‐8. Issue 15 (29th June 2022) - Chen, Rui; Chen, Chengqi; Han, Na; Guo, Wenjing; Deng, Hui; Wang, Yali; Ding, Yanpeng; Zhang, Mengxian
Abstract: Annexin‐1 (ANXA1) is widely reported to be deregulated in various cancers and is involved in tumorigenesis. However, its effects on glioblastoma (GBM) remain unclear. Using immunohistochemistry with tissue microarrays, we showed that ANXA1 was overexpressed in GBM, positively correlated with higher World Health Organization (WHO) grades of glioma, and negatively associated with poor survival. To further explore its role and the underlying molecular mechanism in GBM, we constructed ANXA1shRNA U87 and U251 cell lines for further experiments. ANXA1 downregulation suppressed GBM cell proliferation, migration, and invasion and enhanced their radiosensitivity. Furthermore, we determined that ANXA1 was involved in dendritic cell (DC) maturation in patients with GBM and that DC infiltration was inversely proportional to GBM prognosis. Considering that previous reports have shown that Interleukin‐8 (IL‐8) is associated with DC migration and maturation and is correlated with NF‐κB transcriptional regulation, we examined IL‐8 and p65 subunit expressions and p65 phosphorylation levels in GBM cells under an ANXA1 knockdown. These results suggest that ANXA1 significantly promotes IL‐8 production and p65 phosphorylation levels. We inferred that ANXA1 is a potential biomarker and a candidate therapeutic target for GBM treatment and may mediate tumour immune escape through NF‐kB (p65) activation and IL‐8 upregulation.